Pregnant women's use of e‐cigarettes in the UK: a cross‐sectional survey. (8th November 2020) - Bowker, K; Lewis, S; Phillips, L; Orton, S; Ussher, M; Naughton, F; Bauld, L; Coleman, T; Sinclair, L; McRobbie, H; Khan, A; Cooper, S
Abstract : Objective: To estimate prevalence of vaping in pregnancy. Compare characteristics and attitudes between exclusive smokers and vapers, and between exclusive vapers and dual users (smoke and vape). Design: Cross‐sectional survey. Setting: Hospitals across England and Scotland. Population: Pregnant women attending antenatal clinics in 2017. Methods: Women at 8–24 weeks' gestation completed screening questions about their smoking and vaping. Current or recent ex‐smokers and/or vapers completed a full detailed survey about vaping and smoking. Main outcome measures: The prevalence of vaping, characteristics and attitudes of women who vape and/or smoke. Results: Of 3360 pregnant women who completed screening questions, 515 (15.3%, 95% CI 14.1–16.6) were exclusive smokers, 44 (1.3%, 95% CI 1.0–1.8) exclusive vapers and 118 (3.5%, 95% CI 2.9–4.2) dual users. In total, 867 (25.8%) women completed the full survey; compared with smokers ( n  = 434), vapers ( n  = 140) were more likely to hold higher educational qualifications (odds ratio [OR) 1.51, 95% CI 1.01–2.25). Compared with exclusive vapers ( n  = 33), dual users ( n  = 107) were younger (OR 0.91 95% CI 0.85–0.98) and less likely to hold high qualifications (OR 0.43, 95% CI 0.20–0.96). Compared with smokers, dual users were more likely to be planning to quit smoking (OR 2.27, 95% CI 1.24–4.18). Compared with smokers, vapers were more likely to think vaping was safer than smoking (78.6% versus 36.4%). Conclusions: One in 20 pregnant women report vaping, and most also smoke. Dual users are more motivated towards stopping smoking than smokers. Where women have tried but cannot stop smoking, clinicians could encourage them to consider vaping for smoking cessation. Tweetable extract: One in 20 women report vaping during pregnancy but of those that do vape, most also smoke, despite having intentions to quit. Tweetable extract: One in 20 women report vaping during pregnancy but, of those that do vape, most also smoke, despite having intentions to quit.